Pelatihan Online Penggunaan Geometry Toolbox untuk Mendukung Pembelajaran Jarak Jauh pada Masa Pandemi - Febrian Febrian; Puji Astuti; Rindi Antika (IKIP PGRI Bojonegoro, 2020)
ABSTRACTRegarding the demands of the 4.0 industrial revolution where every math educator must be able to adapt to technological developments and respond quickly to the COVID-19 pandemic, teachers should improve his capacity to use technology. The results of the analysis through partner exploration with a number of teachers who are members of the Mathematics Subject Teacher Conference (MGMP) for the high school mathematics of Bintan Regency found that there is still limited knowledge about technology so that the need for training. Through Community Service (PKM) activities, online training on Geometry Toolbox is carried out, it’s considered to have great potential to support distance learning. Through these activities, a learning video is produced which can be used as a distance learning resource. Four aspects of success of this activity are general assessment, relevance and significance of activities, usefulness, and aspects of increasing the knowledge, understanding and skills of participants. The data obtained by distributing questionnaire using the Google Form platform and questions and answers during activity sessions. The results of this activity show that the online Geometry Toolbox training is going very well where participants have increased knowledge, an understanding of technology integration in mathematics learning and are skilled at using the Geometry Toolbox software in packaging learning. Thus training activities have provided opportunities for teachers to be able to carry out distance learning during the COVID-19 pandemic in 2020. Keywords: distance learning, Geometry Toolbox, online training ABSTRAKTerkait tuntutan revolusi industri 4.0 dimana setiap pendidik matematika harus mampu menyesuaikan diri dengan perkembangan teknologi serta secara sigap merespon situasi pandemi COVID-19, maka guru harus meningkatkan kapasitas dirinya dalam menggunakan teknologi. Melalui penjajakan mitra terhadap sejumlah guru yang tergabung dalam Musyawarah Guru Mata Pelajaran (MGMP) Matematika tingkat SMA Kabupaten Bintan diperoleh informasi bahwa masih ada kelemahan penguasaan teknologi sehingga perlu diadakan pelatihan. Melalui kegiatan pengabdian kepada masyarakat berupa pelatihan online Geometry Toolbox dirasa memiliki potensi besar untuk mendukung pembelajaran jarak jauh. Melalui kegiatan tersebut dihasilkan video pembelajaran yang dapat dijadikan sumber belajar jarak jauh. Empat aspek penentu keberhasilan kegiatan ini adalah penilaian secara umum, relevansi dan signifkansi kegiatan, kebermanfaatan, serta aspek peningkatan pengetahuan, pemahaman dan keterampilan peserta. Data diperoleh dengan penyebaran angket menggunakan platform Google Form serta tanya jawab selama sesi kegiatan. Hasil kegiatan ini menunjukkan bahwa pelatihan online Geometry Toolbox berjalan dengan sangat baik dimana peserta memiliki peningkatan pemahaman mengenai integrasi teknologi dalam pembelajaran matematika serta terampil menggunakan software Geometry Toolbox. Dengan demikian kegiatan pelatihan ini telah mendukung pembelajaran jarak jauh pada masa pandemi 2020.Kata Kunci: pembelajaran jarak jauh, Geometry Toolbox, pelatihan online